EGFR Inhibitors for Neoadjuvant and Adjuvant Therapy of NSCLC - Fabio Villa (Journal of Surgery and Surgical Research - Peertechz Publications, 2015)
5-year survival rates of Non-Small Cell Lung Cancer (NSCLC) remain unsatisfactory after surgery with curative intent and disease recurrences, including distant metastases, are frequent. Only a minority of this heterogeneous disease is positive for EGFR mutations and suitable for Tyrosine Kinase-Inhibitor biological agents, which however present limits in terms of stable response to treatment, due to the acquired drug resistances. A few trials administrating EGFR inhibitors combined with surgery, in neoadjuvant or adjuvant settings, have been reported with lack of evidence. The third-generation EGFR inhibitors, with the amelioration of techniques of gene profiling and the knowledge of pathways could extent the spectrum of complementary-to-surgery treatments in NSCLC at high risk of relapse.